2018
DOI: 10.1111/sdi.12754
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure target for the dialysis patient

Abstract: The appropriate blood pressure (BP) target for dialysis patients remains controversial. Although there have been remarkable advances in this area in the general population, extrapolation of these data to dialysis patients is not possible. Observational studies in dialysis patients suggest that low BP is associated with worse outcomes. However, this is likely a result of confounding, considering that among dialysis patients with fewer cardiovascular comorbidities and longer survival, a more linear relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…However, the evidence to support these recommendations are weak as it was extrapolated from observational studies or data derived from non-ESRD patients (Chang, 2011). On the other hand, studies have reported that a high percentage of patients achieving these targeted blood pressure range suffered from intradialytic hypotension, which may lead to myocardial stunning phenomena and death (McIntyre and Goldsmith, 2015;MacEwen et al, 2017;McCallum and Sarnak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence to support these recommendations are weak as it was extrapolated from observational studies or data derived from non-ESRD patients (Chang, 2011). On the other hand, studies have reported that a high percentage of patients achieving these targeted blood pressure range suffered from intradialytic hypotension, which may lead to myocardial stunning phenomena and death (McIntyre and Goldsmith, 2015;MacEwen et al, 2017;McCallum and Sarnak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hemodiafiltration sessions were delivered three times per week with volumetric dialysis machines (Fresenius Medical Care, model 4008H) and filters F60 and F80 (Fresenius Medical Care, Bad Homburg, Germany). Following our institution policies, hypertension was maintained and controlled by a strict prescription of dry weight, with no antihypertensive drugs (21). All patients were on an unrestricted diet and performed exercise with a stationary bicycle during dialysis sessions.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that where long dialysis and strict salt control is applied hypertension has lower prevalence among dialysis patients [11] [20]. Hypertension in dialysis is multifactorial but sodium and water excess appear to be the major causes [11] [12]. Most of the patients were on sodium restriction.…”
Section: Discussionmentioning
confidence: 99%